RADT-15. FIRST EXPERIENCE WITH MAXIMAL SAFE RESECTION AND GAMMATILE BRACHYTHERAPY AS TREATMENT FOR RECURRENT GLIOBLASTOMA. (12th November 2021) - Gessler, Dominic; Neil, Elizabeth; Shah, Rena; Levine, Joseph; Shanks, James; Wilke, Christopher; Reynolds, Margaret; Ferreira, Clara; Dusenbery, Kathryn; Chen, Clark
Abstract: INTRODUCTION: Gammatile (GT) is a recently FDA-cleared brachytherapy platform with 131 Cs seeds imbedded into a resorbable collagen carrier for surgically targeted radiation delivery. We report the first experience for recurrent glioblastoma patients who underwent GT treatment following surgical resection. METHODS: Twenty-two consecutive patients with 23 isocitrate dehydrogenase (IDH) wild-type glioblastomas (14 second; eight third recurrence) who underwent intra-operative MRI/5-ALA guided maximal safe resection followed by GT placement were prospectively followed. There were 6 methylguanine-DNA-methyltransferase promoter methylated (MGMTm) and 17 unmethylated (MGMTu) glioblastomas. RESULTS: The median hospital stay was one day (range:1-15 days). There was one 30-day readmission (4.5%) for a cerebrospinal fluid leak from the incision site, which resolved with lumbar drainage. There were no other wound complications. One patient (4.5%) suffered new post-operative seizure. Eight patients experienced worsened neurological deficit (8/22 or 36%). While all deficits improved by the 30-day follow-up, 7 of these 8 patients suffered KPS decline due to persistent deficits. There was one 30-day mortality (4.5%) from intracranial hemorrhage secondary to heparinization for an ischemic limb. The median follow-up after GT placement for the remaining 21 patients was 296 days (range:111-931 days). Six months local control (LC) was achieved in 75% of the patients irrespective of MGMT status. Median overall survival (OS) was 715 days for the MGMTu patients, and not reached (>1000 days) for MGMTm patients. These outcomes compared favorably to the published literature (LC: 3-49%; OS MGMTu: 135-285 days; OS MGMTm: 174-564 days) and an age, KPS, extent of resection matched glioblastoma cohort who underwent maximal safe resection without GT at our institution (LC: 52%; OS MGMTu: 462 days; OS MGMTm: 821 days; p=0.0089 and p=0.0271, respectively when compared to the GT treated patients). CONCLUSION: This clinical experience supports the safety and efficacy of GT brachytherapy as a treatment option for recurrent glioblastomas.